2022
DOI: 10.21608/bvmj.2022.153244.1565
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the microbial quality of some chicken meat products in EL-Gharbia governorate, Egypt.

Abstract: A grand total of randomly hundred samples of poultry meat products (fresh pane, luncheon, burger and popcorn) 25 of each were collected from various supermarkets in different cities at Gharbia Governorate, Egypt for bacteriological examination of aerobic plate count, Staphylococcal, Enterobacteriaceae, Psychrotrophic, Coliform and Yeast and Mold counts (cfu/g) which were 3.6×10 5 ± 1.9×10 5 , 4.2×10 2 ±1.2×10, 1.9×10 3 ± 1.1×10 2 , 1.9×10 3 ± 1×10 2 , 4.3×10 2 ± 1.1×10 and 2.2×10 2 ± 2.1×10 in fresh pane, 2.2×… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
1
0
1
Order By: Relevance
“…Also table (1) indicated the incidence of Yersiniaenterocolitica isolated from burger samples as 40%. Our results overlap those obtained by Mousa et al [35], who found that the incidence of Yersinia enterocolitica isolated from meat product samples including beef burger, luncheon, pasterma and sausage were 46, 40, 54 and 34%, respectively. Most common sources for this microorganism could be in factories during preparation of the examined product.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Also table (1) indicated the incidence of Yersiniaenterocolitica isolated from burger samples as 40%. Our results overlap those obtained by Mousa et al [35], who found that the incidence of Yersinia enterocolitica isolated from meat product samples including beef burger, luncheon, pasterma and sausage were 46, 40, 54 and 34%, respectively. Most common sources for this microorganism could be in factories during preparation of the examined product.…”
Section: Resultssupporting
confidence: 80%
“…El-Dosoky et al [32] reported(10%) incidence of Salmonella typhimurium in beef burger. An incidence of 20% and 14% and 5.71% were reported by Edris [34], Mousa et al [35] and Ibrahim et al [36] respectively, which are far less than the incidence observed in the present study in the burger samples. Staphylococcusaureus could cause food poisoning and if it grows in large numbers can leave toxins in the product, which may survive heating.…”
Section: Resultscontrasting
confidence: 71%